Video of a Lesser Black-backed Gull, Bob Cecil, October 20,1986 - Cecil, Robert I.et al (2018)
Video by Bob Cecil of a Lesser Black-backed Gull flying over the Mississippi River below Lock and Dam 19 at Keokuk, Iowa, October 20, 1986. This item is related to an IOU Records Committee review: https://avian.lib.iastate.edu/documents/1029/view. Nikon - camera